2020
DOI: 10.1016/j.jid.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

PAR2 Mediates Itch via TRPV3 Signaling in Keratinocytes

Abstract: Animal studies have suggested that transient receptor potential ion channels and G-protein coupled receptors play important roles in itch transmission. TRPV3 gain-of-function mutations have been identified in patients with Olmsted syndrome, which is associated with severe pruritus. However, the mechanisms causing itch remain poorly understood. Here, we show that keratinocytes lacking TRPV3 impair the function of proteaseactivated receptor 2 (PAR2), resulting in reduced neuronal activation and scratching behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 58 publications
1
68
0
Order By: Relevance
“…In AD patients, the skin is exposed to various proteolytic enzymes from exogenous (e.g., bacteria or house dust mites) or endogenous sources (e.g., tryptase, trypsin and kallikreins, mainly KLK5) that are released by epithelial or immune cells during inflammation processes, highlighting the importance of this pathway in the early disease phases (24,25). Recent findings by Zhao et al (26) revealed intriguingly that PAR-2 activation appears to be located upstream of TSLP and that stimulation of TRPV3 can induce TSLP release. TSLP activates other immune cells, but can also directly stimulate pruriceptive sensory nerve fibers to induce itch (27), a finding that has also been shown for the alarmin IL-33 (28).…”
Section: Alarmins and Neuropeptidesmentioning
confidence: 99%
“…In AD patients, the skin is exposed to various proteolytic enzymes from exogenous (e.g., bacteria or house dust mites) or endogenous sources (e.g., tryptase, trypsin and kallikreins, mainly KLK5) that are released by epithelial or immune cells during inflammation processes, highlighting the importance of this pathway in the early disease phases (24,25). Recent findings by Zhao et al (26) revealed intriguingly that PAR-2 activation appears to be located upstream of TSLP and that stimulation of TRPV3 can induce TSLP release. TSLP activates other immune cells, but can also directly stimulate pruriceptive sensory nerve fibers to induce itch (27), a finding that has also been shown for the alarmin IL-33 (28).…”
Section: Alarmins and Neuropeptidesmentioning
confidence: 99%
“…This suggests that non-PAR2 mediated responses are also important in the pathogenesis of AD. Recently, Zhao et al demonstrated that TRPV3, a warm-temperature-sensitive channel in keratinocytes, modulates PAR2-associated cytokine production, such as TSLP, indicating that PAR2-TRPV3 signaling in keratinocytes play a role in inflammation and pruritus transmission in AD [46]. Two groups have recently shown the regulatory function of neuronal alteration by PAR2 in keratinocytes in a Grhl3 PAR/+ mouse-model overexpressing PAR2 in suprabasal keratinocytes.…”
Section: Protease and Protease-activated Receptors (Pars)mentioning
confidence: 99%
“…Additionally, activation of PAR1 and PAR2 recruit trimeric G proteins (Gi, Gq, or G12/G13) whereas PAR4 signals, through Gq or G12/G13. Gq activation, stimulate further downstream processes including TRPV1 and TRPV3 [ 42 , 88 , 97 , 98 ] ( Table 1 and Table 2 ). If all members of PAR cause itch sensation involving TRPV1 activation or if other G proteins, biased signaling, and additional receptors are engaged remains elusive.…”
Section: Itch Mediators Modulators and Their Receptorsmentioning
confidence: 99%